Identification and quantification of coding and long non‐coding RNAs in stallion spermatozoa separated by density. (17th April 2020) - Ing, Nancy H.; Konganti, Kranti; Ghaffari, Noushin; Johnson, Charles D.; Forrest, David W.; Love, Charles C.; Varner, Dickson D.
Abstract: Background: It is not unusual for stallions to have fertility problems. For many, artificial insemination with more dense spermatozoa (isolated by density gradient centrifugation) results in greater pregnancy rates compared with the rates when using unfractionated spermatozoa. RNAs in spermatozoa delivered to the oocyte at conception are required for embryo development. Novel molecular assays of spermatozoa that reflect function are needed to predict the fertility of stallions. Objectives: To describe and compare the RNA populations in more dense and less dense spermatozoa from stallions. Materials and methods: Spermatozoa from five stallions were separated into more dense and less dense populations by density gradient centrifugation. Complementary DNA libraries were made from each of the ten total RNA samples after ribosomal RNA removal. Next‐generation sequencing characterized the RNA populations in more and less dense spermatozoa. Quantitative reverse transcription‐PCR was used to confirm differential expression of selected RNAs. Results: Stallion spermatozoa contain 11 215 RNAs, with the most prevalent RNA being a 1492 base long non‐coding RNA. The levels of 159 RNAs were greater in more dense spermatozoa, while levels of seven other RNAs were greater in less dense spermatozoa. Quantitative reverse transcription‐PCR confirmed the threefold greater levels of solute carrier family 26 member 8 (SLC26A8) mRNA in less dense spermatozoa, and sixfold and threefold greater expression levels of the SCP2 sterol binding domain containing 1 (SCP2D1) and spermatogenesis‐associated protein 31D1 (SPATA31D1) mRNAs in more dense spermatozoa, respectively. Discussion and conclusion: We identified 11 215 RNAs in stallion spermatozoa and 166 with differential expression between more dense and less dense fractions. Many prevalent RNAs were also found in bull, boar, and human spermatozoa. Many differentially expressed RNAs are known to be testis‐ or spermatozoa‐specific. Our results may lead to identification of an RNA population in spermatozoa that is optimal for establishing successful pregnancies.